Evaluación de control de gestión en una cooperativa de crédito - Zanin, Antonio (2023)
The objective of the study was to assess the perception of two officials in relation to the management control system (MCS) used to assess the performance of a Brazilian Credit Union. For this, a research instrument adapted from two studies by Ferreira and Otley (2006) and Beuren and Teixeira (2014) was applied to 82 employees representing 21.08% of the total number of employees of the cooperative. The data are treated by means of descriptive statistics and information entropy techniques. Among the results, it was observed that the SCG and the performance assessment of the cooperative are consolidated, with a mean response of 4.35, varying from level 4 (partial agreement) to 5 (total agreement). Also, one of the contributions of this study was the fact that it was provided to test in another context and segment the performance management and control instrument restructured by Beuren and Teixeira (2014), validating the proposed adaptation by the aforementioned authors.